Reconstructive surgery for Charcot osteoarthropathy of the calcaneus. A series of clinical cases - Артур Ruslanovich Suleymanov; Stanislav Aleksandrovich Osnach; Victor Gennadievich Protsko; Vladimir Nikolaevich Obolenskiy; Vasiliy Victorovich Kuznetsov; Elena Yuurievna Komelyagina; Nuria Ismailovna Sabantchieva; Sargon Konstantinovich Tamoev; Dmitry Yurievich Borzunov (N.N. Priorov Journal of Traumatology and Orthopedics, 2026)
Materials and methodsInthestudy group of 8 patients, 7 operated on open reconstructive surgery on the calcaneus,1patientoperated on closed deformity correctionandfixationintheIlizarov apparatus.The unloadingperiodwa carried out until radiological signsof consolidation,followed by the dismantling of the device in one patientand the transitionto conservative methods of fixation and unloading. Results.Noearl postoperativecomplicationswere observed in all patients after open reposition(n=7).Thmeteredload wascarried out4.5months after surgeryInthepostoperative period, 1 patient developedinstability of theexternal fixation apparatus (AEF) dueto a violation of the unloading regime and walking withfull support on the operated limb, which required premature dismantlingofthAEF with continued fixation in the TCC. Another patientoperated on with immersionfixators at stage 1 of Eichenholtz had amanifestation of Charcotfoot in ankle joint at the stageof walking with a full load, which require repeated fixation of thefoot and ankle joint for a periodof months.In the future, the patient usedorthopedic individual shoes, repeated surgical interventionswernotrequired.The averagefollow-uperiodwas3.05+0.years.DiscussionDespitethe morefrequent involvementofthe middle part of the foot, it is the involvement of the posterior part of the foot that leads tomore significant biomechanicaldisorderswhichleadsto moredifficultreatment. The rare occurrence indicates the need for a careful approach to diagnosis, since theisolated nature othe lesion may disguise itself as other diseases.The average BMIinour group was 25.8 kg/m2.These indicators are lower than the datareported in theliterature. Itcan be assumed that for the isolated manifestation ofCharcotfoot of the calcaneus, the roleof excess weight as a factor of increased stress may be less significant, or it is compensated by other mechanisms ofosteoarthropathydevelopment.Conclusion.Despite the small sample of patients, the data obtained indicate thepossibility of successful use of reconstructive techniques in isolated osteoarthropathy of thecalcaneus (type 5accordingtoSanders-Frikberg).Thepatient's commitment to treatment should beassessed when deciding whether to perform surgery.Studies with a larger number of patients are needed to form unified recommendations on surgical treatment tactics for this category of patients.